The economic well-being of smallholders and challenges during COVID-19 pandemic: A review - Nurul Atiqah Binti Mohd Suib; Norlida Hanim Mohd Salleh; Mohd Fazim Ahmad (Agricultural Economics (AGRICECON), 2023)
The challenges smallholders face in agricultural management between developed and developing countries differ and can also impact the smallholder's well-being. The purpose of this study is to identify factors that affect the well-being of smallholders. We conducted a systematic literature by applying the Preferred Reported Item for Systematic Review and Meta-Analysis (PRISMA) and extracted 30 articles from Scopus and Web of Science. These articles show three main factors that drive well-being: technology, optimal resource, and insurance, and two additional factors: market pricing and tax policy. Findings show that all the above factors will first impact economic well-being and, subsequently, social well-being. When COVID-19 struck, the smallholder's well-being was also affected in addition to the destabilised food chain. Travel restrictions have led to a labour shortage. The smallholders had to turn to e-commerce to sell their products. They also incurred losses and experienced difficulties in procuring agricultural intermediate inputs. The absence of agricultural insurance worsened the impact on the well-being of the smallholders. To safeguard the well-being of these smallholders, the study suggests that stakeholders should encourage local labour participation, increase investment in human capital, adopt e-commerce in marketing, offer agricultural insurance schemes against various disasters and continuously provide or increase subsidies to smallholders.